Applying Quality Management Tools to Improve the Customer’s Journey at Beauty Salon - Khulood Mahdaly; Mashaer Sheikhoon; Nof Alabdale; Khalid Husain (European Scientific Journal, ESJ, 2025)
Purpose: This paper focuses on assessing and improving the quality of services provided at Beauty Salon in Saudi Arabia. The evaluation covers the entire customer journey, starting from reservation and visiting, through to payment, and finally, providing services. Design, Methodology, Approach: A mixed-method approach was utilized, combining qualitative data from interviews with clients and salon staff, and quantitative data collected through customer satisfaction surveys. Quality Management Tools were applied to analyze the collected data, identify gaps in service delivery, and propose a structured improvement plan tailored to customer expectations. Findings: Service-related issues were categorized into eight main dimensions: facilities, appointment scheduling, price and value,  staff professionalism, responsiveness, human resources, cleanliness, and services. The House of Quality was used to prioritize the top 22 solutions, with relative weights ranging from 2% to 8%. The integration of the voice of the customer and the voice of the staff provided a holistic view of current challenges and improvement opportunities. Originality/Value: This study contributes to the limited literature on applying Quality Management Tools in the beauty and personal care sector in Saudi Arabia. By integrating SERVQUAL dimensions with quality tools, it offers practical guidelines for salon businesses to enhance service delivery and customer satisfaction. It demonstrates how a customer-centric approach can elevate the competitive positioning of salons in the local market through targeted quality interventions.